Legitimacy the state and beyond - Sevel, Michael; Sadurski, Wojciech 1950-; Walton, Kevin (Law teacher) (Oxford University Press, 2019)
Traditionally, legitimacy has been associated exclusively with states. But are states actually legitimate? And in light of the legalization of international norms why should discussions of legitimacy focus only on the nation-state? The essays in this collection examine the nature of legitimacy, the legitimacy of the state, and the legitimacy of supranational institutions. The collection begins by asking: What sort of problem is legitimacy? Part I considers competing theories, in particular the work of John Rawls. Part II looks at the legitimacy of state apparatus, its institutions, officials, and the rule of law, and the future of state sovereignty. Part III expands the scope of legitimacy beyond the state to supranational institutions and international law. Written by theorists of considerable standing, the essays in this volume will be of interest to students and scholars of law, politics, and philosophy looking for ways of approaching the problem of how extra-territorial affairs affect a state's written and unwritten agreements with its citizens in a world where laws and norms with legal effect are increasingly made beyond the state.